Assessing Water Quality for Ecosystem Health of the Babai River in Royal Bardia National Park, Nepal - Sharma, S.; Allen, M.; Courage, A.; Hall, H.; Koirala, S.; Oliver, S.; Zimmerman, B. (Kathmandu University Journal of Science, Engineering and Technology, 2005)
Water quality of the Babai River was assessed through surveying the aquatic invertebrate populations. Study was carried out at Royal Bardia National Park to observe the effect of irrigation dam on water quality through observing the aquatic benthic macro invertebrate’s composition and abundance. The Nepalese Biotic Score (NEPBIOS) method has been used for the biological water quality assessment. Different metrics like Shannon-Wiener Generic Diversity, Diversity Index, Community loss, taxa richness, EPT index, Chironomidae taxa, were also used for assessing the level of impact caused by dam on the aquatic ecosystem health. Considerable variability in macro invertebrate assemblages was found among different sites. Many of the data obtained suggested further analysis but provisional interpretation suggests that all four sites investigated showed signs of pollution. Even the reference site, which was to act as a control, had a high-loading of organic content, perhaps due to soil and debris from the previous year’s monsoon and the presence of poison resulting in large-scale death of aquatic life.